Degredados, desertores e militares à “sociedade de gente de bem” nas fronteiras do Alto Rio Branco 1820-1860 - Ferreira, Daiane Almeida (2020)
This research is based on the analysis of the list of banished, deserters, and military personnel, sent to constitute the enterprises of the Empire of Brazil with respect to the policies of colonization and security of its provinces and borders, specifically in the region of the Province of Amazonas and Alto Rio Branco. Soon, he approached how these actors relate to the Brazilian Imperial State in the century XIX, pointing to the extreme north and its borders, as the stage for the consolidation of these groups. It is important to understand that the penalty of degradation, and justice in Brazil Empire, entered the context of social discipline, turning to a strategy to deal with the demands of the population, therefore, if at a certain time the punishment with degradation served to clean a region of its undesirable residents, during the Imperial period was strategically used by the Empire to remedy the problem in terms of lack of resources for the application of penalties according to the Criminal Code 1830, along with the lack of prisons, the difficulties in the judicial system, due to the lack of civil servants and its slowness, the penalty was also used to remedy the lack of civil servants in the public administration in the most remote regions. In this context, it is pointed out that, particularly, convicts and deserters were for the Empire of Brazil a frequent instrument to populate the territory and compose its troops, thus becoming a link of the Empire, which served itself in the local context, both in its southern and northern borders, the degrading proved to be part of the plans for these regions to ensure possession of these borders. In consonance with the application of the penalty of degrading as a form of exclusion and incorporation, we have the ventures for the use of military and deserters for purposes of colonization, through the policy of the Empire aimed at creating colonies, thus consolidating population nuclei, the colonies were divided into, national, foreign, agricultural, and military, and had the objective of being established in places considered more distant, for purposes of consolidating the sovereignty of the Empire over the region. In this sense, these actors, whether degreed, deserters or military, were important elements in the political, economic, and social construction in regions such as the Province of Amazonas and its borders, the extreme north being one of the great centers of degradation of Brazil, as well as the policies of colonization undertaken by the Empire in the century XIX.